Estudio Etnográfico de Ozogoche, 2016-2019. - Orozco García, Alan Javier (2020)
The research work entitled "Ozogoche Ethnographic Study 2016-2019" it aimed to collect data from the community mentioned above. Through field work in order to understand the daily life of its inhabitants, their culture, their beliefs, customs, traditions and community behavior with society. The methodology was based on a qualitative design, through the use of informationgathering techniques and tools, such as ethnographic study, participating observation and unstructured qualitative interviews in order to use these methods to collect complete speeches from the villagers ofthe community gather information that help in understanding research. With the results obtained it was concluded that the. communities of Ozogoche do not have the ful! support of the cantonal and national authorities, despite being a tourist site it does not have the main essential services and information on its communities and their tourist attractions are very scarce.